Digital Experience, Attendee Engagement, and Event Loyalty in Indonesian Tourism Events - Dendy Sundayana; Ananta Budhi Danurdara; Rudy Parlindungan Siahaan (International Journal of Applied Business and International Management, 2025)
Tourism events in Indonesia are increasingly shaped by digital platforms, online promotion, mobile information access, and social media interaction. This transformation is reinforced by the expansion of event-based tourism initiatives, including Karisma Event Nusantara and the development of Event by Indonesia as a national digital event platform. Despite this growth, limited empirical research explains how digital experience contributes to attendee engagement and event loyalty in tourism events. This study examines the relationships among digital experience, attendee engagement, perceived event value, attendee satisfaction, and event loyalty in Indonesian tourism events. A quantitative survey was conducted among tourism event attendees in Indonesia, and 268 valid responses were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings show that digital experience significantly influences attendee engagement, perceived event value, and attendee satisfaction. Attendee engagement also positively affects perceived event value and attendee satisfaction, while perceived event value and attendee satisfaction significantly influence event loyalty. The study further confirms a significant sequential indirect effect linking digital experience and event loyalty through engagement, perceived value, and satisfaction. These findings position digital experience as part of the attendee value formation process in tourism events